Magic, lies, and deadly pies : a novel - Popp, Misha (Popp, Misha. Pies before guys mystery., 2022)
Daisy Ellery's pies have a secret ingredient: the magical ability to avenge women done wrong by men. The first time she killed a man with a pie, it was an accident. When Daisy finds a letter on her door threatening to reveal her unsavory secret sideline of pie a la murder, it is blackmail? And if so, who is behind it? The upcoming statewide pie contest could be Daisy's big chance to help wronged women everywhere-- if the blackmailer doesn't leave her business, Pies Before Guys, in crumbles. -- adapted from front flap